Critical Pedagogies: An Alternative Proposal for the Transformation of Schools in Colombia in the 21st Century - Mosquera Mosquera, Carlos Enrique (2025)
This reflection is based on the need for a more conscious and continuous implementation of critical pedagogies in the face of the challenges that today's societies face and the problems that require attention in Colombia. Thus, a reflection will be developed on the most relevant criticisms of the traditional educational model, emphasizing the logic of exclusion and control that perpetuate social inequalities. Secondly, the main proposals of critical pedagogies will be addressed, highlighting their transformative potential and the fundamental role of the teacher as an emancipated pedagogical subject. Besides, some concrete opportunities for applying critical pedagogies to promote social and educational changes are offered. Finally, some conclusions will be presented that summarize the most relevant contributions of this reflection, proposing lines of action around critical pedagogies.